Hidden treasures of Camamu Bay, Bahia, Brazil: New records and two new species of Raspailiidae (Porifera, Demospongiae) - Ozga, Aline Vasum; Menegola, Carla (Zootaxa, 2023)
Currently one species of Cyamon Gray, 1867 and one species of Thrinacophora Ridley, 1885 are reported from the Brazilian coast: Cyamon agnani (Boury- Esnault, 1973) and Thrinacophora funiformis (Ridley & Dendy, 1886) respectively. We describe two new sponge species from Camamu Bay, Bahia, Brazil: Cyamon pedroalcoladoi sp. nov. and Thrinacophora melae sp. nov. . The specimens were found in shallow waters (2–3 m), on the sandy bottom with biodetritus. Cyamon perdroalcoladoi sp. nov. has unique spiculation consisting of two kinds of strongyles, five kinds of styles and two kinds of polyactine spicules. Thrinacophora melae sp. nov. is characterized by only one size of strongyles and raphides, and three kinds of styles. Also, the first record of Cyamon agnani from the state of Bahia—726 km north of the type locality—Espírito Santo, Brazil), a plate of spicule set from Western Atlantic species of Cyamon and the redefinition of both genera are included. Taxonomic keys, comparative tables of spicules and the geographic and bathymetric distributions from Western Atlantic Cyamon species and World Thrinacophora are presented.